Persepsi Siswa Terhadap Kemampuan Mengajar Mahasiswa Praktek Pengalaman Lapangan di Madrasah Aliyah Negeri 1 Surakarta - Abbas, Ngatmin; Budiyono, Slamet; Maslachah , Churun (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
This research aims to explore the perceptions of MAN 1 Surakarta students regarding the abilities and professionalism of Student Interns (PPL) from the Mamba'ul 'Ulum Islamic Institute (IIM) in delivering teaching materials. The qualitative research method involved interviews, surveys, and direct classroom observations. The research subjects were PPL students from IIM currently on duty at MAN 1 Surakarta. The research location focused on MAN 1 Surakarta, involving a population of 455 students from grades X, XI, and XII. The results show that the majority of students gave positive ratings to the abilities of PPL students in conducting lessons. Communication skills, the ability to explain materials, and classroom management were aspects highly rated by students. Overall, this research provides insights into students' positive perceptions of the teaching abilities and professionalism of PPL students, offering perspectives for further improvements.